2023
DOI: 10.1107/s2052252523005675
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the driving forces in crystal packing by analysis of electrostatic energies and contact enrichment ratios

Abstract: Hirshfeld surface analysis is a widely used tool for identifying the types of intermolecular contacts that contribute most significantly to crystal packing stabilization. One useful metric for analyzing these contacts is the contact enrichment descriptor, which indicates the types of contacts that are over- or under-represented. In this statistical study, enrichment ratios were combined with electrostatic energy (E elec) data for a variety of compound families. To compute the electrostatic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Numerous papers delve into the analysis of the roles and strengths of N and O in both intramolecular and intermolecular HB interactions. 10–12 For example, Klebe et al compared the strength of N and O atoms as hydrogen bond acceptors in crystalline oxazoles, isoxazoles, methoxypyridines, and oxime ethers. Their study revealed that, within the entire palette of N and O hydrogen-bond acceptors, specific instances exist where O atoms exhibit weaker hydrogen bond donor characteristics compared to N atoms in molecule⋯H 2 O complexes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous papers delve into the analysis of the roles and strengths of N and O in both intramolecular and intermolecular HB interactions. 10–12 For example, Klebe et al compared the strength of N and O atoms as hydrogen bond acceptors in crystalline oxazoles, isoxazoles, methoxypyridines, and oxime ethers. Their study revealed that, within the entire palette of N and O hydrogen-bond acceptors, specific instances exist where O atoms exhibit weaker hydrogen bond donor characteristics compared to N atoms in molecule⋯H 2 O complexes.…”
Section: Introductionmentioning
confidence: 99%
“…13 Jelsch et al observed that strong hydrogen bonds, such as O/N–H⋯N and O/N–H⋯O, exhibit significant enrichment values and possess the most negative electrostatic energies. 10 Hydrogen bonds between HX (X = N, O) donors and push–pull or saturated aminoketone and aminoester molecular fragments exhibit more frequency on oxygen compared to amino nitrogen. 14 Additionally, the presence of different functional groups and specific molecular contexts can further influence the strength and significance of hydrogen bonding interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between fluoride and nanomaterials is usually carried out by electrostatic forces, surface attraction, chemical dissociation, or hydrogen interactions. These interactions cause the adsorption of fluoride by nanomaterials and the separation of the fluoride from the water [22].…”
Section: Introductionmentioning
confidence: 99%